2013
DOI: 10.1371/journal.pone.0056578
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep Debt Elicits Negative Emotional Reaction through Diminished Amygdala-Anterior Cingulate Functional Connectivity

Abstract: ObjectivesSleep debt reportedly increases emotional instability, such as anxiety and confusion, in addition to sleepiness and psychomotor impairment. However, the neural basis of emotional instability due to sleep debt has yet to be elucidated. This study investigated changes in emotional responses that are elicited by the simulation of short-term sleep loss and the brain regions responsible for these changes.Subjects and MethodsFourteen healthy adult men aged 24.1±3.3 years (range, 20–32 years) participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
111
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 70 publications
12
111
2
1
Order By: Relevance
“…[9][10][11][12][13] Researchers have reported that sleep deprivation is associated with subjective symptoms, 12,14,15 such as decreased vigor, 16 stress, 17 anger, 17 aggression, 18 fatigue, 16,17,19 irritability, 20 anxiety, 17,21 depression, 17 headaches, [22][23][24] and cognitive difficulty. 19,[25][26][27][28][29] Most of this evidence comes from experimental studies that deprive healthy people of sleep for 24 or more hours, or restrict sleep over a longer period (eg, 1 week).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Researchers have reported that sleep deprivation is associated with subjective symptoms, 12,14,15 such as decreased vigor, 16 stress, 17 anger, 17 aggression, 18 fatigue, 16,17,19 irritability, 20 anxiety, 17,21 depression, 17 headaches, [22][23][24] and cognitive difficulty. 19,[25][26][27][28][29] Most of this evidence comes from experimental studies that deprive healthy people of sleep for 24 or more hours, or restrict sleep over a longer period (eg, 1 week).…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56] As we learn more about how sleep deprivation affects feedback processing, it may be possible to further isolate and study in the laboratory the mechanisms by which sleep deprivation produces catastrophic errors in ecologically valid contexts outside the laboratory and find ways to manage and overcome this problem. Figure S1-Effect of attentional lapsing on reversal learning decision task performance.…”
mentioning
confidence: 99%
“…Accordingly, PTSD is associated with several cognitive deficits, very important for the development and maintenance of the disorder [106,107]. Neuroimaging studies in PTSD have reported hyporesponsive medial prefrontal cortical regions, hyperresponsive amygdala and smaller hippocampal volume with decreased activation [50,108,109], similar to findings of human and animal sleep deprivation studies [110][111][112]. In addition, animal studies suggest a significant role of circadian rhythmicity and melatonin on homeostasis, neurogenesis and neural activation in these brain regions [113,114].…”
Section: Memory and Cognitive Functionmentioning
confidence: 62%